2001
DOI: 10.1139/b00-157
|View full text |Cite
|
Sign up to set email alerts
|

Differences in wetland plant community establishment with additions of nitrate-N and invasive species (Phalaris arundinacea and Typha ×glauca)

Abstract: Restored prairie pothole wetlands in North America are often enriched by nitrate-N (NO3-N) that has been lost from surrounding agricultural systems. In addition, these wetlands are increasingly colonized by invasive taxa including Phalaris arundinacea L. and Typha ×glauca Godr. To explore the impacts of NO3-N enrichment, suppression by invasive species, and the interaction of these factors on restored communities, we grew native sedge meadow communities from seed in greenhouse mesocosms and subjected them to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 34 publications
9
68
1
1
Order By: Relevance
“…From a floristic point of view, several studies report a loss of diversity during the invasion of a wetland ecosystem (Green & Galatowitsch 2001;Ehrenfeld 2003;Bowles & Jones 2006;Boers et al 2006). Our data do not show such a loss in diversity but this is due to the loss of species with conservation value (according to Habitat Directive -ECE, 93/43 and the Law on Biodiversity of the Tuscany Administration -LR 56/2000, Regione Toscana) and the arrivals of common species with no conservation value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a floristic point of view, several studies report a loss of diversity during the invasion of a wetland ecosystem (Green & Galatowitsch 2001;Ehrenfeld 2003;Bowles & Jones 2006;Boers et al 2006). Our data do not show such a loss in diversity but this is due to the loss of species with conservation value (according to Habitat Directive -ECE, 93/43 and the Law on Biodiversity of the Tuscany Administration -LR 56/2000, Regione Toscana) and the arrivals of common species with no conservation value.…”
Section: Resultsmentioning
confidence: 99%
“…Invasions of Typha spp. generate dense stands with low plant diversity (Green & Galatowitsch 2001;Ehrenfeld 2003;Bowles & Jones 2006;Boers et al 2006) and present a significant threat to wetland biodiversity. Invasion by Typha could lead to the loss of native species and alter ecosystem functioning, particularly affecting nutrient cycling, hydrology, and fire regimes (Vitousek & Walker 1989;Brooks et al 2004;Callaway & Maron 2006;Boers et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Phalaris responds positively to nutrient enrichment. The controlled experiments of Green and Galatowitsch (2001) and Maurer and Zedler (2002) showed that high nutrient treatments increased biomass of Phalaris and increased allocation to aboveground growth. Also Kätterer and Andrén (1999) reported that fertilization decreased the amount of biomass allocated belowground as compared to aboveground biomass.…”
Section: Biomassmentioning
confidence: 99%
“…It is best adapted to low-lying areas subject to short-term flooding. In North America, it is highly vilified as an opportunist that has taken advantage of sedimentation and nutrient loading in wetlands to colonize and form vast monocultures within these ecosystems (Green and Galatowitsch 2001;Maurer and Zedler 2002).…”
Section: Botanical Descriptionmentioning
confidence: 99%